Risk of post-sphincterotomy bleeding in patients with thrombocytopenia. - AbiMansour, Jad P.; Garimella, Vishal; Petersen, Bret T.; Law, Ryan J.; Storm, Andrew C.; Martin, John A.; Levy, Michael J.; Abu Dayyeh, Barham K.; Chandrasekhara, Vinay (Therapeutic Advances in Gastrointestinal Endoscopy, 2023)
Background: Reports suggest that the rate of adverse events (AEs) post-endoscopic sphincterotomy (ES) to be as high as 10%, with gastrointestinal bleeding being most common after post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis. Objective: The aim of this study was to characterize the incidence of bleeding in patients with thrombocytopenia following ES. Design: Retrospective observational cohort study. Methods: Patients with thrombocytopenia (defined as <150,000 platelets/μL) who underwent ES between May 2017 and December 2020 were identified at a tertiary care medical center. The incidence of immediate (intraprocedural oozing >5 min or requiring intervention) or delayed (clinical bleeding with associated hemoglobin drop within 14 days) post-ES bleeding was determined via manual chart review. Results: A total of 221 patients with a mean platelet count of 108,000 ± 13,000 platelets/μL underwent ERCP with ES. Immediate bleeding occurred in 11 (5%) patients with no significant drop in hemoglobin or transfusion requirement. Two patients (0.9%), both of whom were noted to have immediate bleeding, also developed delayed bleeding. Presence of malignancy was associated with an increased risk of bleeding (36.4% versus 11.4%, p = 0.037) while platelet count was not. Conclusion: In a cohort of patients with thrombocytopenia, rates of immediate and delayed bleeding are similar to previously reported AE rates of ES in the general patient population. Careful attention should be given to patients with a history of active malignancy as well as those who develop immediate bleeding as they appear to be at increased risk for bleeding complications. Plain language summary: Risk of bleeding in patients with low platelet counts after sphincterotomy during endoscopic retrograde cholangiopancreatography procedures The sphincter that controls the flow of bile into the small bowel is often cut for a variety of clinical indications (sphincterotomy) during a procedure called endoscopic retrograde cholangiopancreatography (ERCP). One of the complications of this maneuver is bleeding. The physiology of bleeding is complex, and the risk of bleeding cannot be well captured by a single condition or laboratory test. It was presumed that low platelet counts would increase a patient's risk of bleeding during a procedure, but emerging data suggests that many endoscopic procedures are safer than previously understood in these patients. However, there is limited data for sphincterotomy and ERCP. This study from a single, academic center evaluates the outcomes of all patients who underwent sphincterotomy with platelets that were below the normal threshold. Overall, the data shows that sphincterotomy appears to be as safe in patients with low platelets as the general population. Patients with active cancer may be at slightly higher risk for bleeding. Additional precautions may be needed in this group, however further studies are needed to confirm this finding.